Architectural Design Failures A Case Study of BSD Junction and Gianyar People’s Market - Miarsono, Harry (Proceeding International Pelita Bangsa, 2023)
Not every architectural design outcome aligns with the aspirations of both the architect and the client. There are instances where, post-construction and after the buildings have been utilized for a period, they end up deserted, eventually transforming into abandoned structures. Architectural design failure refers to instances where the design of a building, structure, or space is failed, resulting in negative consequences such as safety hazards, functional problems, financial losses, or aesthetic issues. These failures can arise due to various reasons, including inadequate planning, poor design decisions, lack of attention to detail, insufficient consideration of user needs, and sometimes unforeseen circumstances. This study investigates two commercial buildings situated in South Tangerang and Gianyar, Bali. The study's methodology relies on conducting on-site observations using case studies, gathering primary data, and subsequently analyzing the observations' outcomes. Additionally, the study will draw upon the theoretical frameworks of various scholars to substantiate the findings and derive conclusive insights.